Alih Kode dan Campur Kode dalam Acara CCM (Carita Campuruk Makkalak) di TVRI - Risnawati, Risnawati; M., Asia; Nurhusna, Nurhusna (Indonesian Journal of Social and Educational Studies, 2023)
Abstract. The purpose of this study was to describe (a) the form of code-switching and code-mixing in Makassar and Indonesian in the CCM program (carita campuruk makkalak) on TVRI (b) the function of code-switching and code-mixing in Makassar and Indonesian in the CCM program (carita campuruk makkalak) on TVRI from a review of Abdul Chaer's sociolinguistic theory. This research is qualitative research. Data collection techniques in research are observation techniques, note-taking techniques, and documentation techniques. Data analysis in this study includes data reduction, data presentation, and conclusion. The study results show that code-switching in the CCM program (Carita campuruk makkalak) on TVRI includes three forms of language switching. namely the form (1) occurs between sentences (2) occurs intra-sentence and (3) code switching occurs in tags. Forms of code mixing in conversations on CCM (carita campuruk makkalak) on TVRI (1) insertion into tangible elements of words (2) insertion of tangible elements of phrases (3) insertion of tangible elements of clauses. The function of code-switching is (1) to adjust to the interlocutor, (2) to Create an atmosphere of humor, and (3) To clarify speech. Code mixing function (1) To convey information (2) Respect the speech partner (3) To clarify speech. Keywords: code-switching, code mixing, Makassar language, CCM (Carita campuruk  makkalak).